CHALLENGES AND OPPORTUNITIES OF E-GOVERNMENT IN STRENGTHENING THE TRANSPARENCY AND ACCOUNTABILITY OF THE GOVERNMENT - Jackson Yumame (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
The study aims to understand the challenges and opportunities of implementing e-Government in an effort to improve transparency and accountability of government. Digital technology has changed the way government works, and e- Government can play a key role in driving a more democratic and transparent government. However, the implementation of e-Government also faces challenges. Using a literature research approach, the study identifies and analyzes opportunities and challenges in e-Government implementation. Research results indicate that e-government has significant benefits in increasing transparency and accountability through better provision of information to the public, more inclusive decision-making processes, and more efficient public services. However, it was also found that problems such as inadequate infrastructure capacity, cybersecurity issues, as well as cultural and social barriers could undermine the effectiveness of e-Government. Overall, studies show that despite the challenges, the opportunities offered by e-Government in improving governance are substantive, noting that the issues identified need to be addressed with appropriate policies and multi-stakeholder involvement. Further research is suggested to explore the latest applications of technology in e-Government, such as AI and blockchain, and to evaluate these implementations in a broader context, looking at their social, economic, and political implications in depth.